The Future of Election Administration
XXII, 361 p. 12 illus., 7 illus. in color.
Keywords: Stakeholders in the operation of American elections are keenly focused on policy reform, resource allocation, administrative professionalism, voter access and accessibility, equipment security, and system integrity. The Future of Election Administration is an edited volume that gathers the perspectives of today’s most forward-thinking practitioners and experts of policy, advocacy, and research about the importance of particular election practices, the professional and operational challenges that election administrators and voter registrars face, and emerging issues in the field. Through its combination of multiple perspectives to describe, analyze, and anticipate key dynamics and dilemmas as well as its emphasis on the practical aspects of administration, this book makes a unique contribution to the election administration literature.